Evaluation of Surrogate Risk Factors for Severe Progression of COVID-19 in Tobacco Smoking Sub-Population and its Possible Amelioration by Immune Modulators (Global Journal of Medical Research, 2022)
Objectives With emergence of SARS-CoV-2 some researcher have identified Smoking as risk factor for severe outcome of COVID-19 while as other have proposed beneficial role of tobacco based products against as they retards severe progression of disease in smoker subpopulation The major drawbacks of these studies were as majority of these studies were conducted in small cohort so conclusive evidences are lacking Study design This original research paper is based on population based cohort study
Keywords: COVID-19; smoking; mechanical ventilation; hazard analysis and mycobacterium indicus pranii (MIP)